Development and Poverty Reduction A Global Comparative Perspective - Zheng, Yongnian (Taylor & Francis, 2019)
Although the absolute number of poor people in the world has declined significantly in recent decades, poverty reduction continues to be a very important issue. There still are very large numbers of poor people, relative poverty is an increasingly concerning problem, and progress on poverty reduction varies enormously from one part of the world to another. Factors contributing to poverty reduction include economic growth, economic integration, and specific poverty-reduction programs, which are often initiated by Western countries. This book considers poverty reduction from a global perspective. Development and Poverty Reduction looks at a wide range of specific subjects, across all continents. It highlights in particular how the issues are perceived from a non-Western perspective and especially how the rise of China is both having a profound impact on poverty reduction globally and also changing the overall way in which development and poverty reduction are approached.